Investor-led sustainability in corporate governance - Wolf-Georg Ringe (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
The transition to a sustainable economy currently involves a fundamental transformation of our capital markets. Lawmakers, in an attempt to overcome this challenge, frequently seek to prescribe and regulate how firms may address environmental, social, and governance (ESG) concerns by formulating conduct standards. Deviating from this conceptual starting point, the present paper makes the case for another path towards achieving greater sustainability in capital markets, namely through the empowerment of investors. This trust in the market itself is grounded in various recent developments both on the supply side and the demand side of financial markets, and also in the increasing tendency of institutional investors to engage in common ownership. The need to build coalitions among different types of asset managers or institutional investors, and to convince fellow investors of a given initiative, can then act as an in-built filter helping to overcome the pursuit of idiosyncratic motives and supporting only those campaigns that are seconded by a majority of investors. In particular, institutionalized investor platforms have emerged over recent years as a force for investor empowerment, serving to coordinate investor campaigns and to share the costs of engagement. ESG engagement has the potential to become a very powerful driver towards a more sustainability-oriented future. Indeed, I show that investor-led sustainability has many advantages compared to a more prescriptive, regulatory approach where legislatures are in the driver's seat. For example, a focus on investor-led priorities would follow a more flexible and dynamic pattern rather than complying with inflexible pre-defined criteria. Moreover, investor-promoted assessments are not likely to impair welfare creation in the same way as ill-defined legal standards; they will also not trigger regulatory arbitrage and would avoid deadlock situations in corporate decision-making. Any regulatory activity should then be limited to a facilitative and supportive role.
urn:nbn:de:hebis:30:3-652435
Keywords: G28; G34; K22; 330; sustainability; ESG; climate change; capital markets; institutional investors; investor coalitions